Study on Flexural Toughness of Steel Fiber Reinforced Self-compacting Lightweight Aggregate Concrete Under Freeze-thaw Environment - Jingjun LI; Xuelian ZHANG; Zhe LI; Jiarui ZHANG; Zizhao SHI (工程科学与技术)
Objective Fiber-reinforced self-compacting lightweight aggregate concrete (FSLC) is characterized by its lightweight properties, thermal insulation, and excellent frost resistance, making it suitable for applications in buildings prone to freeze-thaw damage in the severe cold and cold regions of the north. Currently, most research focuses on qualitative predictions of the porous properties of the aggregate, highlighting the necessity of studying its frost resistance to promote its application in northern regions.Methods The rapid freeze-thaw test measures the frost resistance of FSLC but does not clarify the fiber reinforcement and toughening effects under freeze-thaw conditions. It remains uncertain whether the conclusions regarding fiber reinforcement and toughening at room temperature apply to the low-temperature freeze-thaw environment. Therefore, based on the rapid freeze-thaw test method, the study first determined the freezing resistance index of the specimens, followed by a bending toughness test after a specified number of freeze-thaw cycles. In an earlier stage, the bending toughness evaluation method proposed by the group was employed to assess the flexural toughness characteristics with a large peak spanwise deflection. This evaluation aimed to clarify the effect of fibers on the frost resistance of self-compacting lightweight aggregates under cold temperature freeze-thaw environments. The study focused on the influence of fibers on the flexural toughness characteristics of self-compacting lightweight aggregate concrete under low-temperature freeze-thaw conditions. A systematic analysis of the enhancement and toughening effects of fibers on different loading phases under various freeze-thaw cycles was conducted to provide theoretical support for applying FSLC in engineering.Results and Discussions Fibers improved their compressive strength to a certain extent when incorporated into SLC. The compressive strength increased and then decreased with the increase in fiber content. At 0.5% fiber content, the compressive strength reached a maximum value of 63.3 MPa, which was 16.8% higher than the compressive strength of the non-doped specimen SF0, measured at 54.2 MPa. However, when the fiber content exceeded 0.5%, the compressive strength of the specimens decreased as the fiber content increased. In addition, the dry apparent density of the concrete specimens showed a monotonically increasing trend with the increase in fiber admixture. The relative dynamic elastic modulus of fiber-reinforced recycled fine aggregate concrete decreased with the increase in freeze-thaw cycles. After 75 freeze-thaw cycles, the relative dynamic elastic modulus of SF0.25 and SF0.50 dropped below 60%, while SF0.75 and SF1.0 remained above 60%. Due to weak interfaces produced by fiber incorporation into concrete, the relative dynamic elastic modulus of SF0 was higher than that of SF0.25 and SF0.5 after 75 freeze-thaw cycles. Following 100 freeze-thaw cycles, the relative dynamic elastic modulus of the unreinforced specimen SF0 surpassed that of the fiber-reinforced specimens SF0.25, SF0.5, SF0.75, and SF1.0. Within the tested freeze-thaw cycles, the mass of each group of specimens increased to some extent. Under bending load, the peak load on the load-deflection curve decreased with the increase in freeze-thaw cycles, and the descending section of the load-deflection curve became more gradual. For the same freeze-thaw cycles, due to the bridging effect of fibers on cracks, the peak load on the load-deflection curve increased with the increase in fiber content, and the descending section of the load-deflection curve tended to flatten. Under different freeze-thaw cycles, the flexural strength of FSLC specimens first decreased and then increased with the increase in fiber content. The flexural strength of the specimen with 0.25% fiber content (SF0.25) was the lowest. Within the specified range of fine steel fiber content (0.25%～1.00%), the initial flexural strength ratio Re,p of FSLC specimens under different freeze-thaw cycles exhibited a "high-low fluctuation" trend with increasing fiber content. When the freeze-thaw cycles were fewer (less than 50), the residual flexural toughness Rrt,C, and the residual flexural strength ratio Rf,C increased with fiber content. However, when the freeze-thaw cycles exceeded 50, these two toughness indicators did not exhibit apparent regular trends. For FSLC specimens without freeze-thaw cycles, the fiber peak front contribution rate Ipre,C increased initially and then decreased with the increase in fiber content, while the fiber peak rear contribution rate Ipost,C exhibited a continuous increase. After freeze-thaw cycles, for specimens SF0.25 and SF0.50, the fiber peak front contribution rate Ipre,C was negative, while the fiber post-peak contribution index Ipost,C did not show a consistent trend with the increase in steel fiber content.Conclusions The research results indicated that increasing the freeze-thaw cycles shows a declining trend in the relative dynamic elastic modulus, while the mass loss rate remains negative, and the mass of the specimens exhibits an increasing trend. Micro-steel fibers enhanced the flexural strength of self-compacting lightweight aggregate concrete under freezing conditions. Within the selected number of freeze-thaw cycles, the initial flexural strength of fiber-reinforced self-compacting lightweight aggregate concrete with varying fiber contents changed irregularly with the increase in freeze-thaw cycles. When the freeze-thaw cycles were fewer than 50, the residual flexural toughness ratio and the residual flexural strength ratio increased with the rise in fiber content. However, when the freeze-thaw cycles exceeded 50, these two toughness indices no longer exhibited significant regularity. For the fiber-reinforced self-compacting lightweight aggregate concrete specimens without freeze-thaw cycles, the fiber pre-peak contribution rate increased first and then decreased with the increase in fiber content, while fiber post-peak contribution rate index showed an increasing trend. After freeze-thaw cycles, the fiber pre-peak contribution rate index and post-peak contribution rate index of fiber reinforced self-compacting lightweight aggregate concrete specimens had no obvious regular change trend with the increase of fiber content.